Hydrological changes regulate fish metacommunity structures and β-diversity patterns in the floodplain lake, China - Yang Liu; Li Lin; Haixin Zhang; Guifang Zhang; Zijun Wu; Yanping Zhang; Bin Kang (Ecological Indicators, 2023)
The metacommunity structures are continuously dynamic, and understanding the temporal species distribution patterns and biodiversity variations will elucidate the metacommunity theory. To examine whether the idealized metacommunity structuring, diversity patterns, and potential driving mechanisms vary among different seasons, we assessed seasonal fish data (i.e., normal, wet, and dry seasons) in the Poyang Lake, the largest freshwater lake in China, by incorporating the Elements of Metacommunity Structure (EMS), β-diversity partitioning, and variance partitioning. The results suggested fish metacommunity displayed quasi-structures, with the quasi-Clemensian paradigm in the normal season and the quasi-Gleasonian paradigm in the wet and dry seasons, indicating the unity of species groups and individualistic species responded weakly to latent environmental gradients, respectively. The highest fish β-diversity occurred in the normal season and the lowest in the wet season with a humped trend. The species abundance replacement process contributed more to the total β-diversity than the nestedness-resultant component among seasons. The variation of the highest Local Contribution to Beta Diversity (LCBD) across seasons indicated the significance of protecting unique habitats. The relative importance of environment and spatial factors on fish metacommunity structure depended on discharge alternation, with a more significant role of spatial structuring occurring in the wet season, whereas predominant environmental filtering in the normal and dry seasons. The seasonal shifts in EMS patterns, β-diversity, and metacommunity assembly rules result from the change in hydrological conditions in the Poyang Lake. This work helps understand seasonal metacommunity dynamics and provides essential information for systematic biodiversity conservation planning in freshwater lakes.